A novel universal neutralizing monoclonal antibody against enterovirus 71 that targets the highly conserved "knob" region of VP3 protein. - Tanja K Kiener; Qiang Jia; Tao Meng; Vincent Tak Kwong Chow; Jimmy Kwang (Public Library of Science (PLoS), 2014)
Hand, foot and mouth disease caused by enterovirus 71(EV71) leads to the majority of neurological complications and death in young children. While putative inactivated vaccines are only now undergoing clinical trials, no specific treatment options exist yet. Ideally, EV71 specific intravenous immunoglobulins could be developed for targeted treatment of severe cases. To date, only a single universally neutralizing monoclonal antibody against a conserved linear epitope of VP1 has been identified. Other enteroviruses have been shown to possess major conformational neutralizing epitopes on both the VP2 and VP3 capsid proteins. Hence, we attempted to isolate such neutralizing antibodies against conformational epitopes for their potential in the treatment of infection as well as differential diagnosis and vaccine optimization. Here we describe a universal neutralizing monoclonal antibody that recognizes a conserved conformational epitope of EV71 which was mapped using escape mutants. Eight escape mutants from different subgenogroups (A, B2, B4, C2, C4) were rescued; they harbored three essential mutations either at amino acid positions 59, 62 or 67 of the VP3 protein which are all situated in the "knob" region. The escape mutant phenotype could be mimicked by incorporating these mutations into reverse genetically engineered viruses showing that P59L, A62D, A62P and E67D abolish both monoclonal antibody binding and neutralization activity. This is the first conformational neutralization epitope mapped on VP3 for EV71.